Satellite channels and social movements: The BBC Persian television’s construction of Iran’s green movement / Mansoureh Ganjian - Mansoureh , Ganjian (2017)
In modern societies, the term of “social movements” is representative of broad social alliance of people who are connected through their collectively shared knowledge and identity to give voice to their concerns by engaging in collective actions. Evidently, media, as an integral part, has been associated with new social movements in departure of collective identity to collective behaviors. Since the social media, due to velocity and amplification in exchange of information, has been received more attention by scholars, the purpose of this study is to prominent the role of transnational TVs, as multi-platform services, in non-democratic countries when political control of internet cause a fundamental shift in form of expressing the protests and grievance by the new media. On that account, this study is an attempt to evaluate the news coverage of the BBC Persian TV (BBCPTV) in 2009 presidential post-election and the Iranian Green Movement, whereas the issue is clouded by the BBCPTV’ claim for unbiased reporting. Increasing the value of citizen journalism and user-generated content (UGC) during the Iran’s political crisis indicates the important role of the BBCPTV as a reliable source of information. It capable the protestors have their voice heard through the world largest broadcaster, when they have limited access to internal media and social networks as well. Drawing on critical discourse analysis (CDA) by applying to Fairclough approach (1989), this article develops a theoretical framework of constructivist approach to explicate whether the BBCPTV discourse, for the period of 2009-2011, has been in line with the Green leaders’ demands and goals. The findings provide confirmatory evidence that the BBCPTV through specific framing, has attempted to validate the movement’s goals and its legitimacy while delegitimize Islamic Republic of Iran.